2014
DOI: 10.1590/0104-6632.20140313s00002307
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin entrapment in poly(vinyl alcohol) dense membranes

Abstract: -Our goal in this study was the immobilization of myoglobin in poly(vinyl alcohol) dense membranes. Glutaraldehyde was investigated both as the crosslinking agent, aiming to increase the membrane stability in aqueous medium, and as the vehicle to bind myoglobin and PVA. Reaction and membrane synthesis were carried simultaneously in mild operating conditions in order to maintain the native protein folding. Membrane characterization comprised the water swelling degree, DSC, TGA, UV-visible spectroscopy, FTIR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since the magnitude of H f is related to the crystallinity degree of the samples, it is safe to argue that the crystallinity degree of the samples decreases as the crosslinking time does. This thermal behavior is attributed to the interaction between the GA molecules and the PVA polymer chains that lead to a decrease in the ability of the PVA polymeric chains to reorder themselves in the form of crystallites that participate in the fusion process, as it has been reported in similar works involving PVA membranes . In fact, excessive crosslinking times have been associated to a PVA branching; which can promote a diminishing on the crystal thickness .…”
Section: Resultsmentioning
confidence: 72%
“…Since the magnitude of H f is related to the crystallinity degree of the samples, it is safe to argue that the crystallinity degree of the samples decreases as the crosslinking time does. This thermal behavior is attributed to the interaction between the GA molecules and the PVA polymer chains that lead to a decrease in the ability of the PVA polymeric chains to reorder themselves in the form of crystallites that participate in the fusion process, as it has been reported in similar works involving PVA membranes . In fact, excessive crosslinking times have been associated to a PVA branching; which can promote a diminishing on the crystal thickness .…”
Section: Resultsmentioning
confidence: 72%
“…A broad band around 3329 cm −1 was linked to O−H stretching from the hydrogen bonded band. 62 The vibration bands between 3000 and 2840 cm −1 were related to the C−H stretching of alkyl groups. 63 The peak at 1142 cm −1 referred to the C−O stretching vibration, which mostly corresponds to crystallinity of PVA.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…This was usually related to polymer chains generated through reaction between hydroxyl side groups and breakage of cross‐links. [ 22,49 ] Tp2 of ZHF (Figure 4(A)[b–d]) were in the range of 334 ± 5°C, which were higher than that of HF by about 50°C. This result indicated that thermal stability of the composite films was improved by loading zeolite.…”
Section: Resultsmentioning
confidence: 99%